Nalar Hukum Imam Shâfi’î tentang Usia Kedewasaan dalam Hak Ijbâr; Rekontruksi dalam Konteks Ke-Indonesiaan - Aufal Hadliq Khaiyyul MW (INSTITUT AGAMA ISLAM BANI FATTAH (IAIBAFA), 2017)
The right ijbâr is the right of father or grandfather to marry off his daughter without having to get permission from the daughter to be married, provided that she is not a widow. When Shâfi’î established the law of the right ijbâr, the social condition of the woman was only domestic at the time. In contrast to now, they have started to spread in the public domain. Focus of this research is the reasoning of Shâfi’î law regarding the rights of marriage guardian ijbâr and its reconstruction in the context of Indonesia. Using the sociology and history approach with the category of normative legal research in the form of library research. A father or grandfather is forbidden to force girls in the realm of marriage. Because it contains the benefit, that is to protect religion, soul, mind, property and honor. As well as women’s habits are different. Age of Shâfi’î, even to the beginning of Indonesian independence only live to become domestic. Now, it is allowed to follow education, have a position even work. This opinion is in accordance with the rules of lâ yunkar taghayyur al-ahkâm bi taghayyur al-azmân, and reinforced by the method mas?lah?ah and ‘urf.